Attitude as a Bridge between Brand Awareness and Purchase Intention: A Bibliometric Analysis of Research Developments and Future Directions - Theresia Ayu Kusuma Iswari; Tony Wijaya; Agung Utama (LifeSciFi, 2026)
This study maps the development of research on the role of attitude mediation in the relationship between brand awareness and purchase intention. Using a bibliometric approach, data were retrieved from the Scopus database covering the period 1997–2025. A total of 96 selected documents were analyzed using VOSviewer to examine the relationships and relevance of keywords, authors, institutional affiliations, and publication sources. The results show a significant increase since 2015 and a peak in productivity in 2023. Major journals include developments in Marketing Science Proceedings, Journal of Business Research, and PLOS ONE, with major contributions from the United States, India, Taiwan, Malaysia, and Indonesia. The results of this study confirm that attitude is a key mediator that connects brand awareness with purchase intent. This research was conducted by integrating the Customer-Based Brand Equity (CBBE) and Theory of Planned Behavior (TPB) frameworks and highlighting the importance of credibility, user digital experience, and brand emotional relationships in building positive consumer attitudes.